Russian Federation : Staff Report for the 2000 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
Macroeconomic developments have been very favorable since early 1999, strengthening in important areas lately. Real GDP has more than recovered from the recession that followed the 1998 crisis and the recovery is gaining momentum, with recent data suggesting that real GDP is growing at an annual rate of 6-7 percent. The strong macroeconomic performance reflects mainly the large real ruble depreciation in 1998, but also the increase in oil prices in world markets and a significant strengthening of fiscal and monetary policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet